Electronic Implementation of Government Agency Performance Accountability System (e-SAKIP) of Regional Device Organization in Bengkulu Provincial Government (Case Study of Efforts to Overcome Delays in Reporting Performance of Regional Development Planning Research & Innovation Agency of Bengkulu Province): Implementasi Elektronik Sistem Akuntabilitas Kinerja Instansi Pemerintah (e-SAKIP) Organisasi Perangkat Daerah Di Pemerintah Provinsi Bengkulu (Studi Kasus Upaya Mengatasi Keterlambatan Pelap - Cendy Sartika Dewi; Evsa Wulan Suri; Edi Darmawi (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Bureaucratic reform is a strategic step to realize good governance, increase capacity, accountability, and the quality of public services. This study aims to analyze the implementation of bureaucratic reform at the Women's Empowerment, Child Protection, Population Control and Family Planning Service (DP3AP2KB) of Bengkulu City in four main aspects: institutions, governance, human resources (HR), and accountability and performance, while also assessing its impact on the quality of public services. This study uses a descriptive method with a qualitative approach. Data were collected through in-depth interviews, non-participant observation, and documentation. Informants in this study consisted of leaders, structural officials, employees within the DP3AP2KB of Bengkulu City, and service users. The data analysis technique used is an interactive model that includes data condensation, data presentation, and conclusion drawing. The theoretical basis of this study is based on Samuel P. Huntington's Modernization and Reform Theory which emphasizes the importance of gradual institutional change. The results of the study indicate that the implementation of bureaucratic reform at the DP3AP2KB of Bengkulu City has been running quite well but still faces several obstacles. From an institutional perspective, the establishment of the UPT P2TP2A (Integrated Service Unit for Victims of Violence) has successfully integrated service functions for victims of violence, making things easier for the public. In terms of governance, cost transparency is considered excellent, as all services are free of charge without any illegal fees. However, in terms of human resources and technology utilization, implementation gaps remain, including limited personnel, slow responses to online complaints (e.g., WhatsApp), the lack of a 24-hour on-call service, and bureaucratic obstacles resulting from the centralization of authority in signing referral letters. Overall, bureaucratic reform has had a positive impact on more integrated case management, although optimizing responsive public services remains hampered by budget and human resource limitations.